2020
DOI: 10.1002/hrm.22037
|View full text |Cite
|
Sign up to set email alerts
|

The virtuous cycle of diversity

Abstract: Based on propositions from the resource dependency theory (RDT), we seek to understand how firms respond to social performance problems through diversity. We consider the impact of negative customer and employee incidents as social performance problems because these incidents represent two critical stakeholders, and because of the potential for such problems to cause a wider impact on the affected firms. Using firm-level longitudinal data across four-time points and a crosslagged panel model (CLPM) to test our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…While focusing on race rather than gender, Denny's restaurant chain is frequently identified as an organization that learned from past mistakes to become more inclusive, with its current initiatives affecting their supply chain as well as their own stores (Adamson, 2000;Estrada, 2020;Fromm, 2020). More generally, Srikant, Pichler and Shafiq (2020) have suggested that a "virtuous cycle" can be initiated when social performance problems become visible in the social space; these problems motivate organizations to appoint more diversity to its board, and board diversity in turn leads to better internal diversity activities.…”
Section: What Cross-space Trajectories Characterize Progress Toward G...mentioning
confidence: 99%
“…While focusing on race rather than gender, Denny's restaurant chain is frequently identified as an organization that learned from past mistakes to become more inclusive, with its current initiatives affecting their supply chain as well as their own stores (Adamson, 2000;Estrada, 2020;Fromm, 2020). More generally, Srikant, Pichler and Shafiq (2020) have suggested that a "virtuous cycle" can be initiated when social performance problems become visible in the social space; these problems motivate organizations to appoint more diversity to its board, and board diversity in turn leads to better internal diversity activities.…”
Section: What Cross-space Trajectories Characterize Progress Toward G...mentioning
confidence: 99%
“…With regards to specific policies, prior research shows that women leaders are more likely to adopt and implement diversity and family-friendly policies (Dobbin et al, 2011;Ingram & Simons, 1995). Other research finds a positive mutually reconstitutive relationship between board diversity, defined more generally, and the adoption of diversity practices (Srikant, Pichler, & Shafiq, 2020). Gender equity policies are not merely about increasing women's representation, although they sometimes are, they are also about ensuing equity and fairness in the allocation of jobs and compensation.…”
Section: Women Directors and Gender Inequalitymentioning
confidence: 99%
“…Building a critical mass of underrepresented individuals, whether in a student body or a workforce, is one of those tipping points of creating a system that positively reinforces itself 23 . In addition, a longitudinal study showed that social performance issues concerning employees and customers prompted greater board diversity within the same firm, which led to greater diversity in management practices, which then became part of an ongoing virtuous cycle 24 . Technology, like other social systems, could benefit from being viewed in this same manner, in which the system itself is redesigned to offer positive reinforcement for a desirable social value, like equity.…”
Section: Ehrs As Sociotechnical Systems Vulnerable To Systemic Racismmentioning
confidence: 99%